2002
DOI: 10.1053/jhep.2002.34133
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of rifamycin SV and rifampicin with organic anion uptake systems of human liver

Abstract: The antibiotics rifamycin SV and rifampicin substantially reduce sulfobromophthalein (BSP) elimination in humans. In rats, rifamycin SV and rifampicin were shown to interfere with hepatic organic anion uptake by inhibition of the organic anion transporting polypeptides Oatp1 and Oatp2. Therefore, we investigated the effects of rifamycin SV and rifampicin on the OATPs of human liver and determined whether rifampicin is a substrate of 1 or several of these carriers. In complementary RNA (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
235
5
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(268 citation statements)
references
References 29 publications
24
235
5
2
Order By: Relevance
“…Previous in vitro studies have shown that rifampicin is an inhibitor of Oatp1a4, Oatp1b2, OATP1B1, and OATP1B3 (44)(45)(46). Rifampicin, an antibiotic mainly used in the treatment of tuberculosis, has been shown to reduce the elimination of BSP and to increase serum-conjugated bilirubin and UCB levels (30,47).…”
Section: Figurementioning
confidence: 99%
“…Previous in vitro studies have shown that rifampicin is an inhibitor of Oatp1a4, Oatp1b2, OATP1B1, and OATP1B3 (44)(45)(46). Rifampicin, an antibiotic mainly used in the treatment of tuberculosis, has been shown to reduce the elimination of BSP and to increase serum-conjugated bilirubin and UCB levels (30,47).…”
Section: Figurementioning
confidence: 99%
“…For example, uptake of ICG is inhibited by rifamycin (Paumgartner, 1975), which is a potent liver OATP inhibitor (Fattinger et al, 2000;Vavricka et al, 2002). In contrast, coadministration of erythromycin and gadoxetic acid was recently found to have no effect on liver imaging (Huppertz et al, 2011).…”
Section: Interaction Of Drugs With Transport Systemsmentioning
confidence: 99%
“…In both scores, plasma bilirubin is a parameter that monitors, among others, transport capacity of hepatocytes and biotransformation, i.e., the detoxifying capacity of the liver. Hepatocyte-mediated detoxification involves four phases: phase 0 represents the uptake of substances into hepatocytes, phase I metabolism of substances, phase II, conjugation and phase III export of substances and/or metabolites from hepatocytes (Petzinger and Geyer, 2006;Vavricka et al, 2002). Hence, transport proteins are key molecular components of the hepatocellular detoxification system (phase 0 and phase III) and consequently of liver function tests.…”
Section: Introductionmentioning
confidence: 99%
“…Many drugs that are potent OATP inhibitors in vitro [e.g., cyclosporine (Letschert et al, 2006) and ritonavir (Annaert et al, 2010)] may cause clinically significant DDIs in vivo; for example, significant increases in the systemic exposure of statins have been reported when these OATP inhibitors are coadministered with statins, which are OATP substrates (Shitara et al, 2003;Kiser et al, 2008). OATP1B3 shares a variety of common substrates with OATP1B1, such as statins (Hirano et al, 2004;Kitamura et al, 2008), rifampicin (Vavricka et al, 2002), and bromosulfophthalein (BSP) (Cui et al, 2001). However, some OATP1B3-specific substrates have been identified, including the octapeptide cholecystokinin 8 (CCK-8) Kullak-Ublick et al, 2001;Hirano et al, 2004).…”
Section: Introductionmentioning
confidence: 99%